Inventing superstition : from the Hippocratics to the Christians - Martin, Dale B., 1954- (Cambridge, Mass. : Harvard University Press, 2004)
"Dale Martin provides the first detailed genealogy of the idea of superstition, its history over eight centuries, from classical Greece to the Christianized Roman Empire of the fourth century C.E. With reference to the writings of philosophers, historians, and medical teachers he demonstrates that the concept of superstition was invented by Greek intellectuals to condemn popular religious practices and beliefs, especially the belief that gods or other superhuman beings would harm people or cause disease. Tracing the social, political, and cultural influences that informed classical thinking about piety and superstition, nature and the divine, Inventing Superstition exposes the manipulation of the label of superstition in arguments between Greek and Roman intellectuals on the one hand and Christians on the other, and the purposeful alteration of the idea by Neoplatonic philosophers and the Christian apologists in late antiquity."--Jacket.
Superstitious Christians -- Problems of definition -- Inventing Deisidaimonia: Theophrastus, religious etiquette, and theological optimism -- Dealing with disease: the Hippocratics and the divine -- Solidifying new sensibility: Plato and Aristotle on the optimal universe -- Diodorus Siculus and the failure of philosophy -- Cracks in the philosophical system: Plutarch and the philosophy of demons -- Galen on the necessity of nature and theology and teleology -- Roman superstitio and Roman power -- Celsus and the attack on Christianity -- Origen and the defense of Chrisianity -- The philosophers turn: philosophical daimons in late antiquity -- Turning the tables: Eusibius, the triumphy in Christianity, and the superstition of the Greeks -- Conclusion: the rist and fall of a grand optimal illusion.
Includes bibliographical references (pages 283-299) and index.
Print version record.
Master record variable field(s) change: 072
Keywords: Philosophy, Ancient; Philosophy and religion -- Greece; Philosophy and religion -- Rome; Superstition -- Religious aspects -- History -- To 1500.; SOCIAL SCIENCE -- Folklore & Mythology; Philosophy, Ancient; Philosophy and religion; Superstition -- Religious aspects; Greece; Rome (Empire); Aberglaube; Antike; Römisches Reich; Griechenland; Bijgeloof; Godsdiensten; Klassieke oudheid; Vroege kerk; RELIGION / History; To 1500; Electronic books; History